Evaluasi Implementasi Sekolah Ramah Anak Menggunakan Pathway Comparison Model - Salam, Ramdani; Rohmah, Putri Adibatur; Pamuti, Pamuti; Nasarudin, Nasarudin (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
This study evaluates the implementation of the Child Friendly School (CFS) program at SMPN 2 Kota Ternate, focusing on analyzing the components of CFS. It employs a qualitative descriptive approach using the Pathway Comparison Model by Kaufman (1990) for evaluation. Data collection techniques include in-depth interviews, observations, and the collection of documentary evidence. The evaluation results indicate that the school has implemented the CFS program with various efforts, such as creating a safe and inclusive learning environment and providing training on children's rights to the educational staff. However, there are several aspects that still require improvement, including the cleanliness of school facilities and the conditions of specific classrooms. Recommendations for improvement encompass strengthening training on children's rights, enhancing the cleanliness of school facilities, renovating classrooms and increasing monitoring and evaluation of the CFS program. The participation of students, parents, and alumni should continue to be promoted through organizations, social media, and regular meetings to support the CFS program.